Auto-amputated ovary- rare cause of intestinal obstruction in a neonate: A case report - Liaqat, Naeem; Imran, Raja Muhammad; Mahomed, Anies (Journal of Neonatal Surgery, 2021)
Background: Congenital ovarian cysts rarely auto amputate. An unusual complication of this event is secondary intestinal obstruction. The mechanism may be consequent to a direct pressure effect or to adhesions induced by the cyst. Case Presentation: A neonate presented with an abdominal mass and intestinal obstruction. On exploration, she had a mass hanging over the small intestine and one ovary was absent. Mass was excised and it turned out to be an auto-amputated ovary Conclusion: Although it is a rare pathology in neonates, surgeons must suspect it, particularly if an ovary is absent.